(untitled) (Hekima Review, 2013)
One of the key problems facing the continent of Africa is lack of durable peace. The continent has experienced violence in various forms for many years. One of the major challenges, which face any attempt to address this problem, is identification of the root causes of violence. By large, there has been a general appeal to religion as one of key factors behind violence in many parts of the continent; and so many people talk of religious violence. Even so, a critical understanding of religion as an authentic institution in the society leaves no room for qualifying violence in itself as something religious. This paper first questions the logical validity of qualifying violence as something religious, and then reflects on the function of religion as a moral conscience of the society.